Emotional intelligence and self-concept as predictors of academic achievement among secondary school Chemistry students in South-East Nigeria - Nkiru Naomi Samuel; Ifeoma G.A. Okonkwo; Onyekachi O. Okonkwo (African Journal of Teacher Education, 2024)
The research investigated the predictive strengths of Emotional Intelligence (EI) and Self-concept (SC), singly and jointly on academic achievement of secondary school chemistry students. The predictive research design was adopted. The sample comprised 300 SS3 students (150female, 150male) drawn through a multistage sampling technique from 10 co-education public schools in South-East, Nigeria. Instrument for data collection was a questionnaire, which has 3 sections; section A is the demographic information, section B is a 33item Emotional Intelligence inventory adapted from Shuttle {1998), while section C is a 60item Self-concept scale adapted from Rastogi (1979). Data was analysed using the standardised multiple linear regression and the hierarchical/stepwise linear regression statistical methods. Results obtained reveal that, EI and SC significantly predict academic achievement of students both singly and jointly. Influence of gender was insignificant with both EI and SC. Based on findings, it was recommended, among others that classroom practices that aid students understanding and management of emotions as well as boost their self-confidence and capability judgement should be explore, initiated and sustained.